2003
DOI: 10.2307/3181044
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Need and Unintended Fertility: Longitudinal Evidence from Upper Egypt

Abstract: : Unmet need for family planning remains a useful tool for identifying and targeting women at high risk of unintended pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 0 publications
1
50
0
Order By: Relevance
“…A possible explanation for this observation is that DHS surveys define unmet need for women who wish to postpone their next pregnancy for at least 2 years, while the majority of our study participants signified their intentions to postpone childbearing by at least 6 months from the time of the survey. However, it is well documented that unmet need in most regions of the world is greater than 25% for the married couples, especially in sub-Saharan Africa 4,14 .…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this observation is that DHS surveys define unmet need for women who wish to postpone their next pregnancy for at least 2 years, while the majority of our study participants signified their intentions to postpone childbearing by at least 6 months from the time of the survey. However, it is well documented that unmet need in most regions of the world is greater than 25% for the married couples, especially in sub-Saharan Africa 4,14 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study in Egypt found that 41% of women using methods to space pregnancy gave birth within 3 years compared with 59% of women not using methods who wanted a pregnancy 33. There will be a cost savings in later years, but it will be reduced because we do not take into account later increases in births that occur when women no longer want to postpone childbearing.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, respondent women are asked, “At the time you became pregnant, did you want to become pregnant then, did you want to wait until later, or did you not want to have any(more) children at all?” A more nuanced way of examining pregnancy intentions and unintended pregnancy risk is to examine women’s motivations to avoid a pregnancy and how this corresponds to modern contraceptive use and subsequent pregnancy experience. This type of analysis has been performed in a small number of studies demonstrating that among women who report that they do not want any (more) children, a sizeable proportion (between 16–29 %) become pregnant in a 2 to 5 year follow-up period [1017]. For example, in a study from Upper Egypt, Casterline and colleagues [17] demonstrate that among women who have an unmet need for limiting (that is they do not want any more children but are not using a FP method), 40 % became pregnant in the 2-year survey interval.…”
Section: Introductionmentioning
confidence: 99%
“…This type of analysis has been performed in a small number of studies demonstrating that among women who report that they do not want any (more) children, a sizeable proportion (between 16–29 %) become pregnant in a 2 to 5 year follow-up period [1017]. For example, in a study from Upper Egypt, Casterline and colleagues [17] demonstrate that among women who have an unmet need for limiting (that is they do not want any more children but are not using a FP method), 40 % became pregnant in the 2-year survey interval. Notably, only 12.5 % of women with a met need to limit (that is, women who do not want any more children and are using a FP method to avoid future childbearing) became pregnant in the follow-up period.…”
Section: Introductionmentioning
confidence: 99%